RidA Proteins Prevent Metabolic Damage Inflicted by PLP-Dependent Dehydratases in All Domains of Life - Jennifer A. Lambrecht (American Society for Microbiology, 2013)
ABSTRACT Pyridoxal 5′-phosphate (PLP) is a coenzyme synthesized by all forms of life. Relevant to the work reported here is the mechanism of the PLP-dependent threonine/serine dehydratases, which generate reactive enamine/imine intermediates that are converted to keto acids by members of the RidA family of enzymes. The RidA protein of Salmonella enterica serovar Typhimurium LT2 is the founding member of this broadly conserved family of proteins (formerly known as YjgF/YER057c/UK114). RidA proteins were recently shown to be enamine deaminases. Here we demonstrate the damaging potential of enamines in the absence of RidA proteins. Notably, S. enterica strains lacking RidA have decreased activity of the PLP-dependent transaminase B enzyme IlvE, an enzyme involved in branched-chain amino acid biosynthesis. We reconstituted the threonine/serine dehydratase (IlvA)-dependent inhibition of IlvE in vitro, show that the in vitro system reflects the mechanism of RidA function in vivo, and show that IlvE inhibition is prevented by RidA proteins from all domains of life. We conclude that 2-aminoacrylate (2AA) inhibition represents a new type of metabolic damage, and this finding provides an important physiological context for the role of the ubiquitous RidA family of enamine deaminases in preventing damage by 2AA. IMPORTANCE External stresses that disrupt metabolic components can perturb cellular functions and affect growth. A similar consequence is expected if endogenously generated metabolites are reactive and persist in the cellular environment. Here we show that the metabolic intermediate 2-aminoacrylate (2AA) causes significant cellular damage if allowed to accumulate aberrantly. Furthermore, we show that the widely conserved protein RidA prevents this accumulation by facilitating conversion of 2AA to a stable metabolite. This work demonstrates that the reactive metabolite 2AA, previously considered innocuous in the cell due to a short half-life in aqueous solution, can survive in the cellular environment long enough to cause damage. This work provides insights into the roles and persistence of reactive metabolites in vivo and shows that the RidA family of proteins is able to prevent damage caused by a reactive intermediate that is created as a consequence of PLP-dependent chemistry.